THE IMPLEMENTATION OF THE NUMBERED HEADS TOGETHER (NHT) MODEL BASED ON QUESTION CARD MEDIA: IMPROVING IRE LEARNING OUTCOMES - Eka Aryani; Farida Farida; Robiyah Nur (Jurnal Bilqolam Pendidikan Islam, 2026)
This study investigates the effect of implementing the Numbered Heads Together (NHT) cooperative learning modelsupported by Question Card media on students’ learning outcomes in Islamic Religious Education (PAI) at SMP Negeri 1 Ambarawa. A quasi-experimental design was employed involving two groups: an experimental group receiving instruction through the NHT model assisted by Question Card media and a control group taught using the conventional lecture-based method. Students’ learning outcomes were assessed through a post-test designed to measure conceptual understanding and critical thinking skills. The data were analyzed using both descriptive and inferential statistics to identify differences in learning outcomes between the two groups. The findings indicate that the NHT model assisted by Question Card media has a statistically significant positive effect on students’ learning outcomes, particularly in promoting classroom engagement and enhancing critical thinking skills. The implementation of this model also fostered a more interactive and collaborative learning environment, enabling students to participate more actively in the learning process and to develop a deeper understanding of the instructional material. This study offers practical and theoretical contributions to the development of media-assisted cooperative learning approaches for improving the quality of Islamic Religious Education instruction at the secondary school level.